ASSESSMENT OF PROBLEM BEHAVIOR EVOKED BY DISRUPTION OF RITUALISTIC TOY ARRANGEMENTS IN A CHILD WITH AUTISM. Issue 2 (8th May 2013) - Leon, Yanerys; Lazarchick, William N.; Rooker, Griffin W.; DeLeon, Iser G.
Abstract A functional analysis suggested that the problem behavior of a 9‐year‐old girl with autism was maintained by gaining the opportunity to restore ritualistic toy arrangements that had been disrupted. Functional communication training and extinction produced clear decreases in problem behavior in 2 contexts: 1 in which we removed a play item, and 1 in which we merely relocated the item and blocked its rearrangement.